2017
DOI: 10.1152/ajpheart.00416.2017
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell senescence with aging in healthy humans: prevention by habitual exercise and relation to vascular endothelial function

Abstract: Cellular senescence is emerging as a key mechanism of age-related vascular endothelial dysfunction, but evidence in healthy humans is lacking. Moreover, the influence of lifestyle factors such as habitual exercise on endothelial cell (EC) senescence is unknown. We tested the hypothesis that EC senescence increases with sedentary, but not physically active, aging and is associated with vascular endothelial dysfunction. Protein expression (quantitative immunofluorescence) of p53, a transcription factor related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
136
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 35 publications
(60 reference statements)
7
136
1
3
Order By: Relevance
“…More recently, we have demonstrated that arteries from older healthy adults and hypertensive patients have greater expression of p21, a marker of senescence, as well as the SASP pro‐inflammatory phenotype . Likewise, endothelial cells sampled from healthy older adults have greater expression of the senescence markers p21 and p16, both of which are correlated with blunted endothelial function . In contrast, older adults that perform habitual exercise (a vasoprotective lifestyle) have normalized endothelial senescent markers and endothelial function .…”
Section: Cell Senescence In Vascular Agingmentioning
confidence: 95%
See 1 more Smart Citation
“…More recently, we have demonstrated that arteries from older healthy adults and hypertensive patients have greater expression of p21, a marker of senescence, as well as the SASP pro‐inflammatory phenotype . Likewise, endothelial cells sampled from healthy older adults have greater expression of the senescence markers p21 and p16, both of which are correlated with blunted endothelial function . In contrast, older adults that perform habitual exercise (a vasoprotective lifestyle) have normalized endothelial senescent markers and endothelial function .…”
Section: Cell Senescence In Vascular Agingmentioning
confidence: 95%
“…22 In contrast, older adults that perform habitual exercise (a vasoprotective lifestyle) have normalized endothelial senescent markers and endothelial function. 22 Lastly, in preclinical rodent models, drugs that remove senescent cells, known as senolytics, improve arterial function in older mice (3 months of treatment starting at 24 months). 23 Therefore, senescent cells are a viable candidate for explaining the upregulation and maintenance of both inflammation and oxidative stress that are seen in aged vessels ( Figure 1).…”
Section: Cell S Ene Scen Ce In Va Scul Ar Ag In Gmentioning
confidence: 99%
“…The rate of arterial biological aging or systemic aging can be modulated by changes in lifestyle, for example, food consumption, cessation of smoking, and physical exercise 11, 12, 13, 14, 15. Calorie restriction (CR) effectively reduces the morbidity and mortality of Fischer 344 rats, which is related to a retardation of arterial stiffening, an improvement of arterial distensibility, and an eventual prolongation of the life span 16.…”
mentioning
confidence: 99%
“…Habitually exercising older adults exhibit lower PWV compared with their sedentary counterparts, and improvements in PWV induced by inhibition of NFκB occur only in sedentary older adults (Jablonski et al., ), suggesting that NFκB activity is restrained by chronic exercise. Habitually exercising older adults also exhibit blunted endothelial senescence and production of SASP components compared with their sedentary counterparts (Rossman et al., ). In a cross‐sectional study, exercise‐trained postmenopausal women exhibited lower CRP when compared with sedentary postmenopausal women; however, the exercise‐trained women did not exhibit improved EDD in either the macro‐ or microvasculature of the forearm (Santos‐Parker et al., ).…”
Section: Interventions To Ameliorate Age‐related Inflammation and Artmentioning
confidence: 99%
“…Building on the base of correlational evidence, two seminal studies directly demonstrate the upregulation of NF B in both venous and arterial endothelial cells of older humans (Donato et al, 2007;Donato, Black, Jablonski, Gano, & Seals, 2008). Furthermore, venous endothelial cells from older adults exhibit increased IL-6, TNF-and the pro-inflammatory chemokine CCL2 (Morgan et al, 2013;Rossman et al, 2017). The upregulation of these endothelial inflammatory factors that are components of the SASP might be attributable to increased age-associated arterial cell senescence (Morgan et al, 2013;Rossman et al, 2017).…”
Section: Direct Evidence Of Age-related Arterial Inflammationmentioning
confidence: 99%